"Coming Together in Mouttalos". Issue 3 (2nd September 2018) - Kyriacou-Petrou, Angela; Hadjisoteriou, Maria; Floridou, Sevina
Abstract: This open-street event in Mouttalos, a residential neighborhood in the center of Paphos, Cyprus, used vacant open spaces for a series of festive activities, events and workshops. Inhabited by Turkish Cypriots until 1974, Mouttalos now provides a "temporary" place of residence for displaced Greek Cypriot refugees. The festival, held in 2017, aimed to generate interest in the underdeveloped area through an enhanced urban experience, and to initiate long-term investment, both social and financial.